Current state and prospects of development of the advertising market in Kazakhstan - Baymuhanbetova, E. E.; Ashirbekova, L. Zh.; Tazhieva, S. K. (Journal of Economic Research & Business Administration, 2016)
The article examines trends in the development of Kazakhstan’s advertising market, the analysis of the main indicators of the advertising market, the recommendations for its development. Analysis of the dynamics of volumes of the advertising market is considered in comparison with the global trends. Also assessed the advertising market in the number of advertisers on the most popular categories of goods and services in the context of a variety of media advertising. The features of the Kazakh advertising market and its main trends of modern development. The main directions of further development of the advertising market. It is necessary to develop the market by increasing the volume of advertising and due to the rising cost of their own advertising space, increase the technological capabilities of production, storage and use of advertising in increasing volumes, create growth opportunities use of advertising in the economy, politics, culture, leading to increase the budget of the leaders in the advertising market and also give an opportunity to promote brands of medium and small advertisers.